Biochemical Profiles of Ocimum gratissimum L. and soil characteristics in the Secondary Forest of Cross River State, Nigeria - M. Etukudo , Mbosowo; A. Ukpe, Richard (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
Background: Ocimum gratissimum L. is one the important leafy vegetables commonly utilized as spices, food nutrient supplements and medicinal herbs. This study was conducted to assess the mineral nutrients and proximate compositions in leaves of O. gratissimum in relation to soil characteristics in the secondary forest of Cross River State, Nigeria. Methods: Leaf samples of O. gratissimum and soil samples were collected from two sampling locations (S1 and S2) at the study area. Standard methods were used to determine the mineral nutrients and proximate compositions in leaves samples of the test plant. Soil physico-chemical properties of the experimental soils were determined. Results: Soil physico-chemical properties of the two sampling locations were characteristics of a typical tropical region. The contents of sodium, potassium, nitrogen, phosphorus, iron, manganese, zinc and lead in leaves of O. gratissimum at sampling location 1 were higher than that of sampling location 2, while the calcium, magnesium, and copper contents leaves of O. gratissimum at sampling location 2 were higher than that of sampling location 1. The moisture, crude fat, crude fiber and crude protein in leaves of O. gratissimum at sampling location 1 were higher than that of sampling location 2, while the ash and carbohydrate contents in leaves of O. gratissimum at sampling location 1 were higher than that of sampling location 2. Conclusion: Variations in soil properties as indicated in this study play a significant role on the nutrient constituents of O. gratissimum grown in the two sampling locations.